2002
DOI: 10.1111/j.1469-8749.2002.tb00830.x
|View full text |Cite
|
Sign up to set email alerts
|

Threshold electrical stimulation (TES) in ambulant children with CP: a randomized double‐blind placebo‐controlled clinical trial

Abstract: A randomized double‐blind placebo‐controlled clinical trial was carried out to determine whether a group of stable children with cerebral palsy (36 males, 21 females; mean age 10 years 11 months, range 5 to 18 years) would improve their motor skills after 12 months of threshold electrical stimulation (TES). Two thirds received active and one third received inactive stimulators. For the primary outcome we constructed a set of plausible motor function tests and studied the change in summary indices of the perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 14 publications
1
31
0
4
Order By: Relevance
“…The intensity of our treatment program was similar to other TES studies that had reported 63% to 100% compliance for 6 to 9 months of treatment [1,2,[8][9][10]. Dali et al [2] found 13 of 82 patients left their study because they lost interest or found the treatment too inconvenient. Complying with an intensive treatment program may be a particular problem for the myelomeningocele population because the caregiver burden for them is already high.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…The intensity of our treatment program was similar to other TES studies that had reported 63% to 100% compliance for 6 to 9 months of treatment [1,2,[8][9][10]. Dali et al [2] found 13 of 82 patients left their study because they lost interest or found the treatment too inconvenient. Complying with an intensive treatment program may be a particular problem for the myelomeningocele population because the caregiver burden for them is already high.…”
Section: Discussionsupporting
confidence: 66%
“…Similarly, no change in motion was observed by Dali et al [2] in TES treatment in children with cerebral palsy. We also found no change in lower extremity sensation.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations